ARCHIVISTICS’ CONCEPT, OBJECT, OBJECTIVES - LUKŠAITĖ, DAIVA (Knygotyra, 2015)
Archivistics has long traditions in Western Europe, whereas in Lithuania it was a part of other country’s archyvistics for a long time. After the restoration of independence in 1990, the situation of archivistics has been changing rapidly in Lithuania. It has become an integral part of Communication and information science instead of being part of history. On the ground of the articles written by archives researchers from West European, English speaking countries and Russia, the concept and development of archivistics are reviewed in the article. Research on archivistics definition has been made as well as the main aspects of its development (from point of view of its object, objectives and methods) have been indicated here. The above mentioned aspects have been considered according to Theo Thomassen attitude towards the development of archivistics. The structure of the archivistics and its relations with other sciences (history, information sciences, law, sociology etc.) are revealed in the article. The interdisciplinary character of archivistics has been shown here too. It has also been discussed how the archivistics has been fixated on the institutional level as well. There is a lack of research on archivistics concept in Lithuania. After the research on definitions used both here and abroad, it should be noted that archivistics in Lithuania might be characterized as the whole of ideas about nature of records created by persons and organizations; principles and methods of management, preservation and research of such a records. The stages of the development of the archivistics and the main research tendencies in Lithuania are indicated in the article. It has been pointed out that archivistics is represented by public organizations in Lithuania and is itself being represented by taking part in the work of international organizations.